Familiarization and Confidence: Factors Affecting Young Learners’ Speaking Test Performance - Wuryaningrum, Rica S (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2018)
Acquiring second language for young learners is a challenging task for them especially when it comes to speaking competence. Speaking may be the hardest competence that young learners have to master as it involves many aspects of language skills such as grammar, vocabulary, pronunciation, fluency at the same time. Young learners find difficulty in expressing their thought and idea in spoken language as they have to combine what is in their mind with the target language and then express it orally. These young learners finds difficulties in expressing their ideas in the target language because they have limited knowledge in vocabulary and grammar while speaking is the key skill in primary school foreign language curricula as the learners develop their social-awareness and become competent speakers of the target language (Toledo & Hoit, 2016).For this reason, some school holds English Proficiency test which include speaking as one of the test. Young learners or primary school students need to practice speaking more as it is the medium through which language is encountered, understood, practiced and learnt, (Cameron, 2001).This study aims to find out what are the factors affecting young learners’performance in speaking test and to find out what problems encountered by young learners in speaking test. This study was done in a private school in West Surabaya, Indonesia and the subjects were 87 students from second grade to sixth grade. The research instruments are questionnaire and interview. This study was expected to help students with their difficulties and improve their speaking skill. Keywords: speaking test, speaking skill, young learners, difficulties